Essays on household and family economics - Jiao, Yang (Kansas State University, 2016)
This dissertation consists of three essays in the field of household and family economics. Specifically, the research focuses on the optimal taxation and household behavior, gender inequality in the labor market during economics transition, and fertility choices and female labor supply. Chapter 1 explores the welfare implications of an optimal tax-transfer schedule to dual-earner couples. A non-cooperative model is used to examine labor supply decisions of married couples to both individual- and joint-based taxation, and the results suggest that the impact of income taxation on family labor supply is largely dependent on spouses' relative wage income. I also investigate the welfare effect of a governmental imposed re-distributive program on both spouses, the simulation results of moving from individual to joint taxation improves both spouses' well-beings and the welfare gain is higher for couples when income gap between the husband and the wife is larger. Chapter 2 empirically examines the impact of privatization reform on gender wage gap in urban labor market based on a comprehensive nationwide survey, the Chinese Household Income Projects (CHIP). We observe, between 1995 and 2007, the gender wage gap rises, and the progress of privatization increases women’s productivity. The results of decomposition suggest that the increase in gender discrimination, which is associated with the rapid growth of non-state sector, contributes to widening gender wage gap. Although privatization increase gender segregation in occupational attainments, it is less obvious that segregation can account for the gender wage gap. In Chapter 3, using the 1979 cohort of the National Longitudinal Survey of Youth (NLSY79), we find mothers earn less on average even after controlling for other wage determinants. The wage penalty associated with motherhood is insignificant in the early career, and arises partly due to mothers accumulating less work experience. As a result, late mothers experience stronger (weaker) returns to work experience before (after) their transition to motherhood. The differentials in returns to work experience are robust to controlling for occupational skill requirements and time spent out of employment.
Keywords: Taxation; Time allocation; Gender wage gap; Urban China; Privatization reform; Family gap